1991
DOI: 10.1243/pime_proc_1991_205_026_02
|View full text |Cite
|
Sign up to set email alerts
|

An Equivalent Reduced Modelling Method and its Application to Shaft—Blade Coupled Torsional Vibration Analysis of a Turbine—Generator Set

Abstract: A coupled vibrating system (for example turbine-generator set), consisting of a main system (for example shaft system) and a sub-system (for example blade system) which are connected at bonding points (for example the centre boss of a blade), is equivalently reduced to a model suitable for analysis. According to this modelling technique, the eigenvalue analysis of the uncoupled flexible sub-system is done first under the assumption of the fixed bonding point. Then, an equivalent mass-spring system is produced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

1992
1992
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 4 publications
0
11
0
Order By: Relevance
“…This preliminary result means that the danger of unstable blade bending vibration due to shaft torsional excitation exists when exposing the system to torsional vibration excitation frequencies that are lower than the blade natural frequency. 4. CONCLUSIONS A non-linear dynamic model for blade bending vibration under the effect of shaft torsional flexibility is considered in this paper.…”
Section: Letters To the Editormentioning
confidence: 99%
See 1 more Smart Citation
“…This preliminary result means that the danger of unstable blade bending vibration due to shaft torsional excitation exists when exposing the system to torsional vibration excitation frequencies that are lower than the blade natural frequency. 4. CONCLUSIONS A non-linear dynamic model for blade bending vibration under the effect of shaft torsional flexibility is considered in this paper.…”
Section: Letters To the Editormentioning
confidence: 99%
“…The effect of shaft torsional flexibility on the vibrations of rotating blades has not been considered in the previous studies. Okabe et al [4] highlighted the necessity for modelling both blade bending and shaft torsional deformations in turbo-machinery. Al-Bedoor [5], based on multi-body dynamic approach, developed a coupled model for shaft-torsional and blade-bending vibrations in rotors.…”
Section: Introductionmentioning
confidence: 99%
“…Crawley et al [5] presented a simplified analytical model for rotating a flexible blade-rigid disc-flexible cantilevered shaft system. Okabe et al [6] addressed an equivalent modeling technique for a blade-shaft system by dividing the system into a shaft plus additional equivalent mass-spring models of blades. Zhang et al [7] presented a method for dynamic analysis of flexible blade-disc-shaft systems by means of the finite element method and a modal synthesis approach.…”
Section: Introductionmentioning
confidence: 99%
“…In the work of [4,5], no special attention was given to the coupling between the shaft torsional and blade bending vibrations. Okabe et al [6] reported a study that emphasized the need for modeling the coupled blade bending and shaft torsional vibrations in turbo-machinery. They developed an equivalent model that coupled shaft-torsional and blade-tangential vibrations.…”
Section: Introductionmentioning
confidence: 99%